DEVELOPMENT OF THE PUGUNG RAHARJO ARCHAEOLOGICAL PARK IN LAMPUNG PROVINCE WITH GEOPARK AND ASTROTOURISM CONCEPT - R Ikhram; Harbowo; Lestari; Agustina; Hutama; Prastyo; Yusuf; Natalia; Muliawati; Muztaba; Puradimadja; Raharto; Malasan (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
Pugung Raharjo Archaeological Park is an archaeological site covering a 30 hectares area in East Lampung Regency, Lampung Province. There is some evidence of the megalithic era, also called the stepped pyramid of Pugung Raharjo discovered in 1957. There are other megalithic buildings from the 12th to 16th centuries AD, including menhirs and dolmen and prehistoric remains dating back to 2500 BC. From a geological perspective, Pugung Raharjo Archaeological Park was built on the extent of vesicular basalt lava of the Sukadana Formation, which is situated above the top of the Sukadana Basalt Plateau. These stones even have a local designation referred to as 'curly stones' because of their rough texture and vesicular holes. Due to its good strength and adhe-sion, the people of East Lampung use this stone as their house foundation. These stone is also used to make pundan berundak, menhirs, dolmen and others. The use of local stone for buildings and daily life tools shows a strong connection between geological and cultural aspects. The Pugung Raharjo Site area is also a very suitable location for astronomical observations because of the low level of light pollution. Moreover, according to history, people have been familiar with astronomy in their daily lives, such as wor-ship, time markers, navigation, or directions. This gives reach to a hypothesis about the possibility of this ancient society's astro-nomical knowledge manifested in determining each object's position in an area with specific constellation patterns. Based on its potential, Pugung Raharjo Archaeological Park is very suitable for developing the Geopark concept, which integrates geological, biological, and cultural aspects.